A lightweight lattice-based group signcryption authentication scheme for Internet of things - XU Chuan; AI Xinghao; WANG Shanshan; ZHAO Guofeng; HAN Zhenzhen (Dianxin kexue)
The 5G era has brought opportunities for the rapid development of the Internet of things. Identity authentication is the basis for ensuring the security of the Internet of things. However, in the face of quantum attacks due to the large number of nodes in the Internet of things, the signcrypt-based identity authentication scheme will consume a lot of resources to generate node keys, which is difficult to meet the low cost requirements of the Internet of things. Therefore, a lightweight lattice-based group signcryption authentication scheme was designed. In the key generation stage, the improved trapdoor diagonal matrix was designed to optimize the original image sampling algorithm required for key generation and reduce the overall time required for generating a large number of keys. In the identity authentication stage, based on the residual Hash lemma and the signcryptic property, the message was signed and encrypted in one logical step at the same time, and the interaction flow of dot multiplication and Hash operation with low frequency was proposed to complete the access authentication performed by the group leader on behalf of the group members. Simulation experiments show that this scheme reduces the number of interactions during the access of Internet of things devices, reduces the computing cost of identity authentication stage, and reduces the total cost of signcryption and decryption by more than 7% compared with the existing schemes. Furthermore, the simulation results prove that this scheme can resist quantum attacks in the Internet of things.